Socioeconomic Impacts of Vegetable Farming under Community-Based Resource Management in Maroamalo, Southwestern Madagascar - Norodiny; Raharinirina Tolojanahary Lucianne Nicole; Defemur Zafiry Velontahina Zafiry; Rodine Manena Bylla; Reveka Mampitohy Fialia; Réné de Rolland Lily-Arison (Bisnis, Jasa dan Keuangan, 2026)
This study aims to analyze the socioeconomic impacts of vegetable farming under community-based resource management in Maroamalo, Southwestern Madagascar. Vegetable farming has emerged as a major income-generating activity promoted by the Soamanampy Vondron'Olona Ifotony (VOI) within the framework of natural resource management transfer. A mixed-methods case study approach was employed, combining household surveys, semi-structured interviews, focus group discussions, field observations, and secondary data analysis. Quantitative data were analyzed using descriptive statistics and value-chain assessment, while qualitative information was examined through thematic content analysis. The results show that vegetable farming occupies 15.71 ha and generates an annual production of 1,645.94 tons, primarily consisting of eggplant, pepper, fotsivody, kimalao, and tomato. Most production (80%) is marketed in Toliara, demonstrating strong integration into regional markets. The annual economic value of production was estimated at 1.08 billion Ariary, with producers capturing approximately 62% of the generated value. In addition to improving household income, vegetable farming creates employment opportunities and supports several actors along the value chain, including transporters, traders, and intermediaries. Survey findings further indicate that local communities perceive vegetable farming as a viable alternative to environmentally destructive activities such as charcoal production and forest clearing. Most respondents reported positive contributions of the activity to biodiversity conservation and community-based resource management. The study concludes that vegetable farming plays a significant role in strengthening rural livelihoods while supporting conservation objectives. Promoting sustainable agricultural practices and improving market access could further enhance the contribution of vegetable farming to rural development and environmental sustainability in community-managed landscapes.